Digital Transformation and Discourses of Change Commodify Finnish Public Education - Lempinen, Sonia; Kiesi, Iida; Nivanaho, Nina; Seppänen, Piia (Springer Nature Link, 2025)
Ecosystemic cooperation among the state, municipalities, and commercial actors is evident in the public education of Finland. The edu-ecosystems can include firm interdependences, value creation, co-specialisation, and co-evolution with an aim to sell products and services to the global market as well as to open up markets in a particular country. Here, we examine the discourses through which commercial actors promote the change or transformation of public education. With support from the state, commercial organisations—whether for-profit, non-profit or private or state-run—have a strong agenda to change ‘old-fashioned’ education into one that better serves the twenty-first century work life. The state and municipalities are gatekeeping the businessing around education, but commercial actors would prefer more opportunities to cooperate with public education institutions. It is noteworthy that commercial actors are gaining greater access to public education policymaking through ecosystems, and hence, have greater influence in redefining and commodifying education. Yet, there is a lack of public conversation about the commodification of public education in Finland.